Physician Social Networks and Variation in Prostate Cancer Treatment in Three Cities - Pollack, Craig Evan (Blackwell Science Inc, 2012)
OBJECTIVE: To examine whether physician social networks are associated with variation in treatment for men with localized prostate cancer. DATA SOURCE: 2004–2005 Surveillance, Epidemiology and End Results-Medicare data from three cities. STUDY DESIGN: We identified the physicians who care for patients with prostate cancer and created physician networks for each city based on shared patients. Subgroups of urologists were defined as physicians with dense connections with one another via shared patients. PRINCIPAL FINDINGS: Subgroups varied widely in their unadjusted rates of prostatectomy and the racial/ethnic and socioeconomic composition of their patients. There was an association between urologist subgroup and receipt of prostatectomy. In city A, four subgroups had significantly lower odds of prostatectomy compared with the subgroup with the highest rates of prostatectomy after adjusting for patient clinical and sociodemographic characteristics. Similarly, in cities B and C, subgroups had significantly lower odds of prostatectomy compared with the baseline. CONCLUSIONS: Using claims data to identify physician networks may provide an insight into the observed variation in treatment patterns for men with prostate cancer.